1988
DOI: 10.1002/bjs.1800750420
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peritoneal tube grafts in the inferior vena cava of the pig

Abstract: A tube graft 2.5 or 5 cm long, was constructed from the peritoneum of the anterior abdominal wall of 12 pigs. It was anastomosed end-to-end as an interposition graft in the infrarenal vena cava. The observation period was 4 months. Three of the six short grafts were venographically patent at 2 weeks, while all the long grafts were occluded. After 4 months two short grafts had recanalized, giving a patency rate of five out of six short grafts. No long grafts recanalized. In three of the patent specimens no clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…[9] Vein wall defects longer than 2.5 cm may not be amenable to this repair technique. [10] Although a minimum gluing zone of 0 to 2 mm provided successful hemostasis in four of our five experimental animals, a broader zone all around the patch is necessary for safe hemostasis. An insufficient gluing zone may be present wherever a squirt of blood appears on removal of the sponge used for compression, but the absence of a squirt of blood after the compression period does not exclude the presence of a narrow gluing zone.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[9] Vein wall defects longer than 2.5 cm may not be amenable to this repair technique. [10] Although a minimum gluing zone of 0 to 2 mm provided successful hemostasis in four of our five experimental animals, a broader zone all around the patch is necessary for safe hemostasis. An insufficient gluing zone may be present wherever a squirt of blood appears on removal of the sponge used for compression, but the absence of a squirt of blood after the compression period does not exclude the presence of a narrow gluing zone.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study has shown that a peritoneal tube may successfully replace a 2.5 cm segment of the vena cava, but longer tubes will undergo thrombotic occlusion. [10] Vein wall defects longer than 2.5 cm may therefore not be amenable to this repair technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APF is readily available and the harvesting and fashioning of the graft can be easily performed in a short time. Experimental data have demonstrated that the inner peritoneal mesothelial surface has a low thrombogenic potential and induces rapid endothelialization …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there are mesothelial linings on the inner side of its closed lumen 14. Ribbe et al15 reported that such a mesothelial lining was antithrombogenic and that it also promoted endothelialization. These characteristics of the opened round ligament could be advantageous for its use as a vascular patch graft, including its use in the low‐pressure venous system.…”
Section: Discussionmentioning
confidence: 99%